Answer:
The value of x is .
Step-by-step explanation:
It is given that the inverse variation equation is
..... (1)
The value of y is 4 and the value of k is 7.
Substitute y=4 and k=7 in equation (1).
Divide both sides by 4.
Therefore the value of x is .
9514 1404 393
Answer:
a. 405
b. -2
c. 5
d. 43
Step-by-step explanation:
I don't like doing arithmetic any more than you do, so I let a calculator do it for me. A spreadsheet works well for this, too. The function values are shown in the attachment.
Put the function argument where the variable is and do the arithmetic.
a. h(4) = 5·3^4 = 405
b. d(2) = 7 -9(2 -1) = -2
c. h(0) = 5·3^0 = 5
d. d(-3) = 7 -9(-3 -1) = 43
Answer:
-2, -6
Step-by-step explanation:
using cramer rule
5 -3
-2 -1
calculatiing the determinant = (5 x-1) - (-3x-2) = -5 -(6) = -5-6=-11
using cramer rule
to calculate x we change the coefficient of x with the answer (8,10)
8 -3
10 -1
we calculate determinant = (8x-1)-(-3x10) = -8-(-30) = -8+30 =22
to calculate x
22/-11= -2
to calculate y we change the coefficient of y with the answer (8,10)
5 8
-2 10
we calculate determinant = (5x10)-(8x-2) = 50 -(-16) = 50 +16=66
to calculate y
66/-11= -6
BD = 2x-4
But it's also BE - CE + CD
BE is 3x-1
CE is 2x-3
CD is 2
so
BD = 3x-1 -(2x-3) +2
simplified
BD = 1x +4
since BD = BD (obviously), we can also say that the righthand sides of the two equation must be equal
2x -4 = 1x +4
let's solve for x and that put it into either of the 2 equations.
2x -4 = 1x +4
subtract 1x on both sides
x -4 = 4
add 4 on both sides
x = 8
substitute x for its value in 2x -4 = 1x +4
(this way we double check BD in two expressions at once. the equation should come out true, meaning same value for BD in each expression. both sides should be equal).
2*8 -4 = 1*8 +4
12 = 12
seems true
BD is safely 12